2016
DOI: 10.1039/c6ra18977f
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl based pyrazoline derivatives with vanillic core: synthesis and investigation of their biological properties

Abstract: Synthesis of four novel series of ferrocenyl based pyrazoline derivatives with vanillic core are described and microbiological, BSA and DNA binding studies conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…Previous studies have also shown that the use of vanillin compounds as starting materials in organic synthesis led to the formation of several vanillin-derivatives with a wide spectrum of biological activities [ 10 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that the use of vanillin compounds as starting materials in organic synthesis led to the formation of several vanillin-derivatives with a wide spectrum of biological activities [ 10 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In medicinal chemistry, 2-pyrazoline acts as a privileged scaffold due to its presence in numerous important medical and biochemical agents that have been effectively utilized as antibacterial, antifungal, anti-inflammatory, analgesic, antiparasitic, antiviral, antitubercular, anticancer, anesthetic, and insecticidal agents. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Recently, a 4,5-unsaturated pyrazoline ring called pyrazole has marked its versatile use in the drug design, and it has been found to have a remarkable presence in various potential anticancer molecules such as celecoxib, SC5584. Liu et al [23] have confirmed that celecoxib induces apoptosis in the human osteosarcoma cell line and enhances the cytotoxic effect of cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Trp134 is in a solvent-exposed region of subdomain IB and is highly accessible, whereas Trp213 is buried in the hydrophobic pocket near the drug binding site in subdomain IIA. Most investigations carried out on the interaction serum albumin with compounds have shown biological activity, which have been reported in the literature [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%